Risk Factors For Caesarean Section due to Cephalopelvic Disproportion at Sakubva Hospital in Mutare District Manicaland Zimbabwe - Olivier, Sundika Makengo; Muchirewesi, David; Mukuzunga, Munyaradzi; Mahamane Salissou, Maiboge Tanko (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Cephalopelvic disproportion ( CPD) is one of the commonest indication of caesarean section (CS) . Failure to recognize cephalopelvic before or during labor is associated with fatal complications on the pregnant mother and the foetus . The average caesarean rate at Sakubva district hospital from 2018 to 2020 was 36.4% which is higher above compared to the Zimbabwean national C/S rate of 6 % and the WHO recommended CS rate of 10-15 % . The present increase in CS at Sakubva district is alarming and is a major concern, hence there is need to investigate the major risk factor which could have influenced its rising. Therefore, the present study aimed to investigate the various risk factors associated with caesarean section with regard to CPD at Sakubva district hospital in 2021.An analytic cross-sectional study was used taking data from January to December 2021 to investigate risk factor associated with caesarean section due to cephalopelvic disproportion at Sakubva district Hospital. Data were collected from the theatre and delivery register where records of 1950 cases of CS (348 cases of CS due to CPD and 1602 cases CS with no CPD) in 2021 were conveniently selected. Quantitative data were analysed using Epi Info™ version 7.2.5.0 . The overall prevalence of caesarean section due to CPD was 18% and major risk factors associated with caesarean section due to CPD (P< 0.05) were maternal age ≤18 years (OR 2, 95% CI 2 - 3.5), primigravida (OR 1.6, 95% CI 1.2 -2.2), gestational age ≥40 weeks (OR 2.1, 95% CI 1.6 – 2.6) , being unreferred (OR 3, 95% CI 1.9 -4.6), residing in rural area (OR 2.9, 95% CI 2.2-3.7), ANC visit < 4 (OR 1.4, 95% CI:1.1- 1.8) maternal height ≤150 cm (OR 20.5, 95% CI :7.6-54.8). High prevalence of CS due to CPD was found in this study, significant risk factors associated were mainly maternal but not neonatal which could have adverse maternal and perinatal outcome therefore intervention such as proper antenatal screening of patient with risk factors and health education, training of health workers, use of partograph and timely CS is needed.